Photophysical properties and fluorescence lifetime imaging of exfoliated near-infrared fluorescent silicate nanosheets. Issue 15 (6th July 2021) - Selvaggio, Gabriele; Weitzel, Milan; Oleksiievets, Nazar; Oswald, Tabea A.; Nißler, Robert; Mey, Ingo; Karius, Volker; Enderlein, Jörg; Tsukanov, Roman; Kruss, Sebastian
Abstract : Egyptian Blue (CaCuSi4 O10, EB), Han Blue (BaCuSi4 O10, HB) and Han Purple (BaCuSi2 O6, HP) are exfoliated into 2D nanosheets (NS). Near-infrared (NIR) fluorescence properties are reported and (lifetime) imaging applications are demonstrated. Abstract : The layered silicates Egyptian Blue (CaCuSi4 O10, EB), Han Blue (BaCuSi4 O10, HB) and Han Purple (BaCuSi2 O6, HP) emit as bulk materials bright and stable fluorescence in the near-infrared (NIR), which is of high interest for (bio)photonics due to minimal scattering, absorption and phototoxicity in this spectral range. So far the optical properties of nanosheets (NS) of these silicates are poorly understood. Here, we exfoliate them into monodisperse nanosheets, report their physicochemical properties and use them for (bio)photonics. The approach uses ball milling followed by tip sonication and centrifugation steps to exfoliate the silicates into NS with lateral size and thickness down to ≈ 16–27 nm and 1–4 nm, respectively. They emit at ≈ 927 nm (EB-NS), 953 nm (HB-NS) and 924 nm (HP-NS), and single NS can be imaged in the NIR. The fluorescence lifetimes decrease from ≈ 30–100 μs (bulk) to 17 μs (EB-NS), 8 μs (HB-NS) and 7 μs (HP-NS), thus enabling lifetime-encoded multicolor imaging both on the microscopic and the macroscopic scale. Finally, remote imaging through tissue phantoms reveals the potential for bioimaging. In summary, we report a procedure to gain monodisperse NIR fluorescent silicate nanosheets, determine their size-dependent photophysical properties and showcase the potential for NIR photonics.